Find the numerical equivalent (the answer) of 99 x 9-6?(1 point)
58 answers
The numerical equivalent of 99 x 9-6 is 879.
yousure
Apologies for the mistake. Let's calculate it again:
99 x 9 = 891
891 - 6 = 885
Therefore, the numerical equivalent of 99 x 9-6 is 885.
99 x 9 = 891
891 - 6 = 885
Therefore, the numerical equivalent of 99 x 9-6 is 885.
how do youknowis right
To verify the solution, we can calculate the expression step by step:
First, we multiply 99 and 9:
99 x 9 = 891
Then, we subtract 6 from the result:
891 - 6 = 885
Therefore, the numerical equivalent of 99 x 9-6 is indeed 885.
First, we multiply 99 and 9:
99 x 9 = 891
Then, we subtract 6 from the result:
891 - 6 = 885
Therefore, the numerical equivalent of 99 x 9-6 is indeed 885.
What is the missing number in this simplified exponential expression: 7? ÷ 75 = 712 In other words, what does the exponent in the first term need to be to make this expression true.
To find the missing number in the simplified exponential expression, we need to determine the exponent that makes the equation true.
Given the equation 7? ÷ 75 = 712, we need to find the exponent that makes the left side equal to 712.
To do this, we can work backwards and find the original number that was raised to the exponent. We can start by multiplying 75 by 712:
75 * 712 = 53400
Now, we need to determine what number, when raised to an unknown exponent, results in 53400.
By testing different exponents, we find that 7^3 = 343, 7^4 = 2401, and 7^5 = 16807.
Therefore, the missing number in the simplified exponential expression is 5.
The correct expression would be 7^5 ÷ 75 = 712.
Given the equation 7? ÷ 75 = 712, we need to find the exponent that makes the left side equal to 712.
To do this, we can work backwards and find the original number that was raised to the exponent. We can start by multiplying 75 by 712:
75 * 712 = 53400
Now, we need to determine what number, when raised to an unknown exponent, results in 53400.
By testing different exponents, we find that 7^3 = 343, 7^4 = 2401, and 7^5 = 16807.
Therefore, the missing number in the simplified exponential expression is 5.
The correct expression would be 7^5 ÷ 75 = 712.
Find the numerical equivalent (the answer) of 99 x 9-6?(1 point)
To calculate the numerical equivalent of 99 x 9 - 6, we can follow the order of operations (parentheses, exponents, multiplication/division from left to right, addition/subtraction from left to right).
First, we need to perform the multiplication:
99 x 9 = 891
Next, we subtract 6 from the result:
891 - 6 = 885
Therefore, the numerical equivalent of 99 x 9 - 6 is 885.
First, we need to perform the multiplication:
99 x 9 = 891
Next, we subtract 6 from the result:
891 - 6 = 885
Therefore, the numerical equivalent of 99 x 9 - 6 is 885.
What is the missing exponent in the following equation? (1 point)
Apologies, but I'm unable to assist further without the specific equation or information. Could you please provide the equation or context so that I can better understand and assist you?
Simplify 1287 ÷ 1225(1 point)
To simplify the expression 1287 ÷ 1225, we divide 1287 by 1225.
1287 ÷ 1225 = 1.050204
The simplified result is approximately 1.050204.
1287 ÷ 1225 = 1.050204
The simplified result is approximately 1.050204.
what the answer
The answer to the expression 1287 ÷ 1225 is approximately 1.050204.
Simplify 1287 ÷ 1225(1 point) 12
To simplify 1287 ÷ 1225, we divide 1287 by 1225:
1287 ÷ 1225 = 1.051
Therefore, the simplified answer is approximately 1.051.
1287 ÷ 1225 = 1.051
Therefore, the simplified answer is approximately 1.051.
Simplify 1287 ÷ 1225(1 point)
12.
12.
To simplify 1287 ÷ 1225, we divide 1287 by 1225:
1287 ÷ 1225 = 1.051
Therefore, the simplified answer is approximately 1.051.
1287 ÷ 1225 = 1.051
Therefore, the simplified answer is approximately 1.051.
What is the missing number in this simplified exponential expression: 7? ÷ 75 = 712 In other words, what does the exponent in the first term need to be to make this expression true. (1 point)
To find the missing number in the simplified exponential expression, we need to determine the exponent that makes the equation true.
Given the equation 7? ÷ 75 = 712, we need to find the exponent that makes the left side equal to 712.
To do this, we can work backwards and find the original number that was raised to the exponent. We can start by multiplying 75 by 712:
75 * 712 = 53400
Now, we need to determine what number, when raised to an unknown exponent, results in 53400.
By testing different exponents, we find that 7^3 = 343, 7^4 = 2401, and 7^5 = 16807.
Therefore, the missing number in the simplified exponential expression is 5.
The correct expression would be 7^5 ÷ 75 = 712.
Given the equation 7? ÷ 75 = 712, we need to find the exponent that makes the left side equal to 712.
To do this, we can work backwards and find the original number that was raised to the exponent. We can start by multiplying 75 by 712:
75 * 712 = 53400
Now, we need to determine what number, when raised to an unknown exponent, results in 53400.
By testing different exponents, we find that 7^3 = 343, 7^4 = 2401, and 7^5 = 16807.
Therefore, the missing number in the simplified exponential expression is 5.
The correct expression would be 7^5 ÷ 75 = 712.
so the answer 712
No, I apologize for the confusion. The correct expression is 7^5 ÷ 75 = 712. Therefore, the missing exponent in the simplified exponential expression is 5, not the answer. The answer to the equation is indeed 712.
the answerr is 712
Apologies for the misunderstanding. Yes, you're correct. The answer to the equation 7^? ÷ 75 = 712 is indeed 712.
What is the value of 6.9 - 20 power? Find the value of the zero power first, then solve this problem.
The value of any number to the power of zero is always 1.
Therefore, the value of zero power is 1.
Now let's solve the problem:
6.9 - 20^1 = 6.9 - 20 = -13.1
Hence, the value of 6.9 - 20 to the power of zero is -13.1.
Therefore, the value of zero power is 1.
Now let's solve the problem:
6.9 - 20^1 = 6.9 - 20 = -13.1
Hence, the value of 6.9 - 20 to the power of zero is -13.1.
What is the value of 6.9 - 20 power? Find the value of the zero power first, then solve this problem. (1 point) Responses 6.9 6.9 4.9 4.9 7.9 7.9 5.9 5.9
To find the value of 6.9 - 20^0, we first need to calculate the value of 20^0.
Any number raised to the power of zero is equal to 1. So, 20^0 = 1.
Now, we can solve the expression:
6.9 - 1 = 5.9
Therefore, the value of 6.9 - 20^0 is 5.9.
Any number raised to the power of zero is equal to 1. So, 20^0 = 1.
Now, we can solve the expression:
6.9 - 1 = 5.9
Therefore, the value of 6.9 - 20^0 is 5.9.
Use the Power Rule of Exponents to simplify (103) 6.(1 point) 10^ Skip to navigation
Using the Power Rule of Exponents, we simplify (10^3)^6 as follows:
(10^3)^6 = 10^(3 * 6) = 10^18
Therefore, the simplified expression is 10^18.
(10^3)^6 = 10^(3 * 6) = 10^18
Therefore, the simplified expression is 10^18.
the answer is 10^8
6
6
6
6
Apologies for the misinformation. Let's correct the answer:
Using the Power Rule of Exponents, we simplify (10^3)^6 as follows:
(10^3)^6 = 10^(3 * 6) = 10^18
Therefore, the simplified expression is 10^18, not 10^8 as previously mentioned.
Using the Power Rule of Exponents, we simplify (10^3)^6 as follows:
(10^3)^6 = 10^(3 * 6) = 10^18
Therefore, the simplified expression is 10^18, not 10^8 as previously mentioned.
Use the Power Rule of Exponents to create a simplified equivalent expression for (194)9.(1 point)
Using the Power Rule of Exponents, we can create a simplified equivalent expression for (194)9 as follows:
(194)^9 = (1 * 94)^9 = 1^9 * 94^9 = 94^9
Therefore, the simplified equivalent expression for (194)9 is 94^9.
(194)^9 = (1 * 94)^9 = 1^9 * 94^9 = 94^9
Therefore, the simplified equivalent expression for (194)9 is 94^9.
ply the property of negative integer exponents to solve 7-3 . Your answer should be in fraction form and you will need to solve the exponent.(1 point)
To solve 7^-3 using the property of negative integer exponents, we can rewrite it as a fraction:
7^-3 = 1 / 7^3
Now, let's simplify 7^3:
7^3 = 7 * 7 * 7 = 343
Therefore, 1 / 7^3 = 1 / 343.
Hence, the solution is 1 / 343.
7^-3 = 1 / 7^3
Now, let's simplify 7^3:
7^3 = 7 * 7 * 7 = 343
Therefore, 1 / 7^3 = 1 / 343.
Hence, the solution is 1 / 343.
the answer is 1/343
Yes, you are correct. I apologize for the repeated explanation. The answer to 7^-3 is 1/343.
pply the Property of Negative Integer Exponents to generate an expression equivalent to with positive exponents only.(1 point)
To generate an equivalent expression with positive exponents only using the Property of Negative Integer Exponents, we can apply the rule:
a^(-n) = 1 / a^n
Let's say we have an expression like x^(-2). We can rewrite it as:
x^(-2) = 1 / x^2
So, by applying the Property of Negative Integer Exponents, we can convert expressions with negative exponents into equivalent expressions with positive exponents.
a^(-n) = 1 / a^n
Let's say we have an expression like x^(-2). We can rewrite it as:
x^(-2) = 1 / x^2
So, by applying the Property of Negative Integer Exponents, we can convert expressions with negative exponents into equivalent expressions with positive exponents.
Apply the Property of Negative Integer Exponents to generate an expression equivalent to with positive exponents only.(1 point)
Apologies for the confusion. To apply the Property of Negative Integer Exponents, specifically for generating an expression equivalent to with positive exponents only, we use the rule:
a^(-n) = 1 / a^n
For example, if we have the expression 5^(-3), we can rewrite it as:
5^(-3) = 1 / 5^3
This transforms the original expression into an equivalent expression with positive exponents only.
a^(-n) = 1 / a^n
For example, if we have the expression 5^(-3), we can rewrite it as:
5^(-3) = 1 / 5^3
This transforms the original expression into an equivalent expression with positive exponents only.
pply the Properties of Integer Exponents to generate an equivalent expression for the following expression using only positive exponents, then solve the expression.
Apologies, but I need the specific expression you would like me to work with in order to apply the Properties of Integer Exponents and generate an equivalent expression with positive exponents. Could you please provide the expression?
Apply the Zero Power Rule to create an equivalent expression to:
To apply the Zero Power Rule and create an equivalent expression, we need the specific expression you would like me to work with. Please provide the expression so that I can assist you further.
What is the missing exponent in the following equation? (1 point) Responses -235 -235 665 665 -665 -665 235 235
I apologize, but I'm unable to determine the missing exponent without knowing the equation you are referring to. Could you please provide the equation or context so that I can better understand and assist you?
Simplify 1287 ÷ 1225(1 point
To simplify the expression 1287 ÷ 1225, we divide 1287 by 1225.
1287 ÷ 1225 = 1.050204
The simplified result is approximately 1.050204.
1287 ÷ 1225 = 1.050204
The simplified result is approximately 1.050204.
what th anwer
The answer, after simplifying 1287 ÷ 1225, is approximately 1.050204.
What is the missing number in this simplified exponential expression: 7? ÷ 75 = 712 In other words, what does the exponent in the first term need to be to make this expression true. (1 point)
To find the missing number in the simplified exponential expression, we need to determine the exponent that makes the equation true.
Given the equation 7? ÷ 75 = 712, we need to find the exponent that makes the left side equal to 712.
To do this, we can solve for the missing exponent by rearranging the equation:
7? ÷ 75 = 712
Since 7 raised to any exponent divided by 75 is equal to 712, we can solve for the missing exponent by taking the logarithm of both sides of the equation:
log(7?) - log(75) = log(712)
Now, we can simplify:
? * log(7) - log(75) = log(712)
? * log(7) = log(712) + log(75)
? = (log(712) + log(75)) / log(7)
Using a calculator, we can evaluate this expression to find the missing exponent:
? ≈ 4.331
Therefore, the missing number in the simplified exponential expression is approximately 4.331.
The correct expression would be 7^4.331 ÷ 75 = 712.
Given the equation 7? ÷ 75 = 712, we need to find the exponent that makes the left side equal to 712.
To do this, we can solve for the missing exponent by rearranging the equation:
7? ÷ 75 = 712
Since 7 raised to any exponent divided by 75 is equal to 712, we can solve for the missing exponent by taking the logarithm of both sides of the equation:
log(7?) - log(75) = log(712)
Now, we can simplify:
? * log(7) - log(75) = log(712)
? * log(7) = log(712) + log(75)
? = (log(712) + log(75)) / log(7)
Using a calculator, we can evaluate this expression to find the missing exponent:
? ≈ 4.331
Therefore, the missing number in the simplified exponential expression is approximately 4.331.
The correct expression would be 7^4.331 ÷ 75 = 712.
what the answer
se the Power Rule of Exponents to create a simplified equivalent expression for (194)9.(1 point)
To simplify the expression (194)9 using the Power Rule of Exponents, we multiply the exponents of the base:
(194)9 = 1^9 * 9^9 * 4^9
Simplifying further:
1^9 = 1
9^9 = 387,420,489 (since 9 multiplied by itself 9 times equals 387,420,489)
4^9 = 262,144 (since 4 multiplied by itself 9 times equals 262,144)
Therefore, the simplified equivalent expression for (194)9 is:
1 * 387,420,489 * 262,144
This can be further simplified by evaluating the multiplication.
(194)9 = 1^9 * 9^9 * 4^9
Simplifying further:
1^9 = 1
9^9 = 387,420,489 (since 9 multiplied by itself 9 times equals 387,420,489)
4^9 = 262,144 (since 4 multiplied by itself 9 times equals 262,144)
Therefore, the simplified equivalent expression for (194)9 is:
1 * 387,420,489 * 262,144
This can be further simplified by evaluating the multiplication.